The new economic governance of the Eurozone : a rule of law analysis - Dermine, Paul (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
The Eurozone and the European Union have recently been confronted with a number of existential threats. The sovereign debt crisis and the COVID-19 pandemic have forced European decisionmakers to pass important reforms which have radically transformed the nature and scope of the Union's powers in the field of economic and fiscal policy. As the new economic governance of the Eurozone emerges as the main driver of integration in today's Europe, this book seeks to assess the solidity of the constitutional foundations supporting that system, and its compliance with the Union's core founding value: the rule of law. Using competence allocation, regulatory quality, access to external review and fundamental rights sustainability as analytical benchmarks, this book argues that the recent metamorphosis of Eurozone economic governance has not been accompanied by a parallel strengthening of its constitutional settlement, leading to a problematic misalignment between the Union's action and its governing principles.
Introduction -- The new economic governance of the Eurozone : structure and functioning -- Post-crisis economic policy coordination in the Eurozone : a conceptual appraisal through the governance perspective -- The new economic governance of the Eurozone and the competence allocation system -- The internal quality of the new economic governance of the Eurozone : the case of fiscal policy rules -- The new economic governance of the Eurozone and the (im)possibilities of external review -- The new economic governance of the Eurozone and the sustainability of EU fundamental rights -- Conclusion : the rule of law, the role of law and economic governance in the Eurozone.
Title from publisher's bibliographic system (viewed on 18 Jul 2022).
Keywords: Constitutional law -- Economic aspects -- European Union countries; Rule of law -- Economic aspects -- European Union countries; Eurozone -- Political aspects; European Union countries -- Economic policy